Social Issues in IMF-Supported Programs - Khemani, Ritha (Occasional Papers; Occasional Paper ;, 2000)
As part of its mandate, the IMF seeks to create the conditions necessary for sustained high-quality growth, which encompasses a broad range of elements. These include sound macroeconomic policies, growth-enhancing structural reforms, good governance, and such social policies as cost-effective social safety nets and targeted social expenditures. This paper reviews the IMF's policy advice in two key areas of social policy: social safety nets and public spending on education and health care. It was initiated as part of the work by the World Bank and IMF to strengthen the poverty focus of adjustment programs in low-income countries, in particular within the framework of the Initiative for Heavily Indebted Poor Countries (HIPCs).